Pivot task increases knee frontal plane loading compared with sidestep and drop-jump - Cortes, N.; Onate, J.; Van Lunen, B. (Journal of Sports Sciences, 2011)
The purpose of this study was to assess kinematic and kinetic differences between three tasks (drop-jump, sidestep cutting, and pivot tasks) commonly used to evaluate anterior cruciate ligament risk factors. Nineteen female collegiate soccer athletes from a Division I institution participated in this study. Participants performed a drop-jump task, and two unanticipated tasks, sidestep cutting and pivot. Repeated-measures analyses of variance were conducted to assess differences in the kinematic and kinetic parameters between tasks. The pivot task had lower knee flexion (-41.2 ± 8.8°) and a higher valgus angle (-7.6 ± 10.1°) than the sidestep (-53.9 ± 9.4° and -2.9 ± 10.0°, respectively) at maximum vertical ground reaction force. The pivot task (0.8 ± 0.3 multiples of body weight) had higher peak posterior ground reaction force than the drop-jump (0.3 ± 0.06 multiples of body weight) and sidestep cutting (0.3 ± 0.1 multiples of body weight), as well as higher internal varus moments (0.72 ± 0.3 Nm/kgm) than the drop-jump (0.14 ± 0.07 N/m/kgm) and sidestep (0.17 ± 0.5 N m/kgm) at peak stance. During the pivot task, the athletes presented a more erect posture and adopted strategies that may place higher loads on the knee joint and increase the strain on the anterior cruciate ligament.